Binasal hemianopia in two sisters. Issue 1 (21st January 2020) - Scotcher, Sam; Morphis, George; Good, Peter
Abstract : Binasal hemianopia is a rare visual field defect. A teenage girl presented with blurred vision and persistent headaches following a minor head injury. The ocular examination was normal except for a binasal hemianopia, and subsequent neuroimaging was also unremarkable. Her older sister was found to have the same visual field defect, also with normal neuroimaging. This represents the first reported case of binasal hemianopia found in siblings. Given that no neurological or ocular cause was identified in either sister, this supports the theory of an unknown congenital aetiology.